EAL teacher agency: implications for participation in professional development. Issue 1 (2nd January 2016) - Gurney, Laura; Liyanage, Indika
Abstract: Teachers construct their practice, education and professional development within two domains of professionalism: sponsored and independent. The association between these two domains, however, is complex; it is overlapping, inseparable and sometimes uneasy. The complexity is further exacerbated by the codependent nature of association between the teacher and employment context in which teachers' and institutions' trajectories for professional development may vary. This situation calls into question the discrete treatment given to and received by sponsored and independent professionalism in conceptualisations of teacher professional development. We argue that, in both domains, teachers' agency as learners is crucial for their professional development and institutional efficacies. We critique the ostensible disconnect and tensions that exist between the domains of sponsored and independent professionalism in relation to teaching English as an additional language and discuss how principles of sponsored and independent professional development initiatives can be harnessed for optimal teacher learning.